Living conditions and coping strategy of coastal communities contribute to the environmental integrity at the world heritage site of Dungonab Bay Mukkawar Island Marine National Park at the Sudanese Red Sea coast - Nahid Abdel Rahim Osman; Eldirdery Abeadallah Abdelrahman Ibrahim (Journal of Fisheries, 2022)
World natural heritage sites (WNH) are those areas recognised for their unique natural resources and/or processes. The main objective of this study was to investigate the living conditions and diversity of livelihoods of coastal communities of the world natural heritage site of the Dungonab Bay-Mukkawar Island Marine National Park (DMNP-WNH). The fishing communities at Dungonab and Mohamed Gol villages were found to be deprived in water, electricity, education, health care, sanitation, flooring, cooking fuel and other livelihood assets. The expenditure of 82.9% of Dungonab and 91.2% of Mohamed Gol households exceeded their income. Accordingly, DMNP-WNH fishers were not able to invest in their livelihood assets and they used hook and line as the sole fishing gear. These conditions have restricted the access of respondents to fishing grounds. About 95% of Dungonab and 93.7% of Mohamed Gol respondents were experiencing extreme poverty. The quality of life at study sites was discouraging for human settlement, therefore, limiting the population growth and consequently the consumption of natural resources at DMNP-WNH. This has positively contributed to the environmental integrity. Access to clean water, electricity and diversification of fishermen livelihoods are of key importance to stimulate blue economy and sustain the environment of the DMNP-WNH.